Optimal power flow model for building integrated photovoltaic systems operating in the Andean range - Andres Julian Aristizabal; Daniel Ospina; Mónica Castaneda; Sebastian Zapata; Edison Banguero (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a novel model to evaluate the power output of a building integrated photovoltaic system (BIPVS) operating in the Andean Range.  The Optimal Power Flow (OPF) model optimizes the power output of the BIPVS within an electrical system without violating operational limits.  The model is validated with the experimental performance of a 6 kW BIPVS installed in Bogota, Colombia. The meteorological data affect the power flow. The model is evaluated under sunny and rainy days to characterize the photovoltaic array performance. The results showed that the AC PV-energy generation was 5,904 kWh/year for 2017 and that there is a correlation factor of 99.87% between the experimental power flow and the proposed model.